Internal and marginal fits of 3D-printed provisional prostheses: comparative effect of different printing parameters - Al-Dulaijan, Yousif A.; Aldamanhori, Rand; Algaoud, Hadeel; Alshubaili, Rand; Alkhateeb, Reem; Alalawi, Haidar; Abualsaud, Reem; Alqarawi, Firas K.; Al-Qarni, Faisal D.; Gad, Mohammed M. (Frontiers in Oral Health, 2024)
ObjectivesThe influence of printing parameters on the marginal and internal fit of three-dimensional (3D) printed interim fixed partial dentures (IFPDs) has been understudied. This investigation sought to elucidate the impact of printing orientation and post-curing time on these critical factors.MethodsA total of 260 3-Unit IFDPs were printed using two different resins (130/NextDent C&B MFH and 130/ASIGA DentaTOOTH). For each material, specimens were printed with three different angulations (0-, 45-, and 90-degree in relation to the z-axis). Each was further divided into 4 groups (n = 10) according to post-curing time (30-, 60-, 90-, and 120 min), while the green state (GS) group at 0-degree remained without post-curing as a control. Each specimen was scanned and then superimposed on the original CAD file. The marginal and internal fit of premolar and molar restorations were evaluated using the silicone replica technique. Digital scanning of the master die, both with and without a fit checker, was followed by data superimposition to compare the master die with the fit checker of each sample. 3D comparisons were conducted using initial and best-fit alignment methods, and the root mean square error (RMS) was calculated to quantify marginal and internal fit at each abutment and for the overall restoration. Statistical analysis was performed using JMP® software (JMP®, Version 16, SAS Institute Inc., Cary, NC, USA, 1989–2022) with a significance level 0.05 for all tests.ResultsFor the ASIGA group, 0-degree orientation generally exhibited better fit than 45- and 90-degree orientations, with some variations based on post-cure time. For marginal fit, ASIGA crowns typically showed better results with 90-degree orientation, while NextDent crowns demonstrated consistent performance across orientations. Post-curing time also influenced marginal fit, with longer durations generally resulting in improved outcomes.ConclusionWith different printing orientations and post-curing times, ASIGA and NextDent resins can produce IFDPs with acceptable internal and marginal fit. However, NextDent resin consistently outperformed ASIGA in terms of overall fit. Further research is needed to evaluate the long-term clinical performance of these materials.